Early coronary angiography in patients with myocardial infarction without ST elevation after out-of-hospital cardiac arrest: a systematic review and meta-analysis - Ahmed, Warda; Ejaz, Arooba; Arshad, Muhammad Sameer; Mubeen, Manahil; Ahmed, Aymen; Siddiqui, Asad Ali; Tharwani, Zoaib Habib; Deepak, F. N. U.; Kumar, Prince; Shahid, Izza; Memon, Muhammad Mustafa (Frontiers in Cardiovascular Medicine, 2024)
BackgroundEarly coronary angiography (CAG) in post-cardiac arrest patients without ST-segment elevation is a topic of debate. This meta-analysis aimed to assess its impact on outcomes.MethodsA search of Medline and Cochrane up to February 2023 was conducted to identify randomized controlled trials and observational studies comparing patients undergoing early CAG vs. delayed/no CAG after experiencing out-of-hospital cardiac arrest. A random-effects model pooled odds ratios (ORs) with 95% confidence intervals (CIs). Meta-regression explored factors modifying effect sizes.ResultsWe identified 16 studies (7 RCTs, 9 observational studies) involving 4,737 patients. Early CAG significantly reduced long-term mortality [OR: 0.66 (0.51–0.85)], and increased favorable cerebral performance category (CPC) 1–2 at discharge [OR: 1.49 (1.09–2.03)]. Observational study subgroup showed decreased short-term mortality, long-term mortality, and CPC 1–2 at discharge, unlike RCT subgroup. Meta-regression revealed type 2 diabetes mellitus and follow-up time influencing short-term mortality and CPC 1–2 at discharge, respectively.ConclusionEarly CAG in post-cardiac arrest patients without ST elevation is associated with long-term clinical benefits, particularly evident in observational studies. Interpretation should be cautious.